Re/thinking harmonization in the Commonwealth Caribbean : audiences, actors, interests and educational policy formation - Jules, Tavis Deryck (ProQuest LLC Ann ArborUS, 2008)
Investigates whether educational policies at the national level were geared towards national, regional and or international audiences. Examines which policies audiences, national policies have targetted, whether this focus has shaped policy intentions and have been incorporated into institutional practices.